Investigation on the immunomodulatory activities of Sarcodon imbricatus extracts in a cyclophosphamide (CTX)-induced immunosuppressanted mouse model - Fanxin Meng; Panju Xu; Xue Wang; Yu Huang; Liyan Wu; Yiling Chen; Lirong Teng; Di Wang (Elsevier, 2017)
Aims: Sarcodon imbricatus, an edible fungus, is widely used in Asian medicine because of its significant pharmacological activities. In the present study, we investigated the immunomodulatory effects of polysaccharide-enriched S. imbricatus extracts (SP) in cyclophosphamide (CTX)-induced immunosuppressed mice. Results: Astragalus polysaccharide (AP) was used as a positive control. Compared with CTX-induced immunosuppressed mice, thirty-day SP treatment strongly enhanced the organ indexes of spleen and thymus and suppressed hind paw swelling. Both AP and SP increased the serum levels of immunoglobulin (IgA, IgG, and IgM), and suppressed the overproduction of interleukin-2 (IL-2). Moreover, SP reduced methane dicarboxylic aldehyde levels, and increased the total antioxidant capacity, superoxide dismutase, and glutathione peroxidase in both serum and liver tissues of CTX-induced immunosuppressed mice. Conclusion: S. imbricatus extracts significantly improved immune function in CTX-induced immunosuppressed mice via modulation of oxidative systems. Keywords: Sarcodon imbricatus, Immunity, Cyclophosphamide, Oxidation